pH-Responsive Membranes: Biomedical Applications - Singh, Randeep; Mondal, Piyal; Purkait, Mihir Kumar (CRC Press, 2022)
The book provides an application-oriented approach for pH responsive membranes, a type of stimuli responsive membrane and their applications in the biomedical field including initial development and recent use. It explains types, modes, and modification methods of membranes along with membrane usage in applications such as drug delivery, haemodialysis, chemical sensing and so forth. The potential research carried out in the area as well as future scope is discussed, that provides better insights to the readers about the subject ranging from the basics to the advanced level of the topic. Describes preparation, characterization, and applications of pH responsive membranes in biomedical applications. Introduces the theoretical understanding of the pH responsiveness. Covers advancement of techniques regarding pH responsive membranes. Provide insights for the development of new materials and membranes. Discusses advancements in drug delivery, haemodialysis, antibodies and enzyme production, chemical sensing and selective ionic transport using pH responsive membranes. This book is aimed at graduate students, researchers involved in membrane/chemical engineering/polymer research, and medical researchers.